2022
DOI: 10.5455/msm.2022.34.272-277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Patients with Diabetes Standard of Care in the Jazan Region, Saudi Arabia

Abstract: Background: COVID-19 patients with DM have increased mortality and severity of the disease. Although telemedicine helps to minimize the impact of COVID-19 on the DM standard of care, it is increasingly evident that COVID-19 has a significant impact on DM standards of care, especially in areas where telemedicine is not available. Objective: The study aimed to assess the impact of COVID-19 on patients with diabetes standard of care in the Jazan region, Saudi Arabia. Methods: A cross-sectional study using an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Difficulties in glucose management may be due to common barriers reported in both local and international studies, which have mentioned that adherence and access to healthcare services was decreased during the pandemic. A cross-sectional study conducted in Jazan, KSA, involving 394 patients found that the COVID-19 lockdown significantly reduced the levels of compliance, medical treatment, and lifestyle habits among Saudi patients with diabetes [ 49 ]. A one-year follow-up study examined the impact of the COVID-19 pandemic on diabetes self-management globally.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in glucose management may be due to common barriers reported in both local and international studies, which have mentioned that adherence and access to healthcare services was decreased during the pandemic. A cross-sectional study conducted in Jazan, KSA, involving 394 patients found that the COVID-19 lockdown significantly reduced the levels of compliance, medical treatment, and lifestyle habits among Saudi patients with diabetes [ 49 ]. A one-year follow-up study examined the impact of the COVID-19 pandemic on diabetes self-management globally.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in glucose management may be due to common barriers reported in both local and international studies which have mentioned that adherence and access to healthcare services was decreased during the pandemic. A cross-sectional study conducted in Jazan, Saudi Arabia, involving 394 patients found that the COVID-19 lockdown significantly reduced the levels of compliance, medical treatment, and lifestyle habits among Saudi patients with diabetes [30]. A one-year follow-up study examined the impact of the COVID-19 pandemic on diabetes self-management globally.…”
Section: Discussionmentioning
confidence: 99%
“…The Raosoft calculator (Raosoft Inc., Seattle, WA) [19] was employed to ascertain the sample size. Based on a 95% confidence level, a margin of error of 5%, an anticipated response rate of 50%, and a total diabetic patient count of 39,000 in Jazan [20], the smallest required sample size was determined to be 381.…”
Section: Sampling Methods and Sample Sizementioning
confidence: 99%